Toleransi Antar Umat Beragama Dalam Struktur Organisasi Subak Air Satang Desa Medewi Kecamatan Pekutatan Kabupaten Jembrana (Perspektif Pendidikan Agama Hindu) - Gusti Ayu Kade Cintya Susanti (Jayapangus Press, 2018)
The Subak Air satang organization is one of three Subak organizations in Medewi Village located in Banjar Pesinggahan, Medewi Village, Pekutatan District, Jembrana Regency. The existence of the Satang Subak Air organization is a subak of the subak organization that is in the community of people who are Hindu and Islamic. The uniqueness of the Subak Medewi Organization is because of other people, namely Islam who participated in the members of Satang Subak Air. The tolerance between religious communities in the organizational structure of subak air satang is something positive that should be used as a guideline for every citizen or religious community in preventing conflicts that are nuanced by sara. Tolerance between religious people is very useful to build solidarity between the diversity of ethnicity, race, religion, ethnicity and culture among us. If this inter-religious tolerance has truly been applied to every society, surely a prosperous, peaceful, peaceful life that is the dream of every citizen or religious community can be created.